Silica Magnetite Adsorbent: Effect of Drying Temperature of Silica Sol Gel on Magnetite Core Structure - Endang Sawitri; Choiril Azmiyawati; Parsaoran Siahaan (Jurnal Kimia Sains dan Aplikasi, 2018)
Recently, magnetite was investigated as water purification adsorbent because it’s unique magnetic properties that improved the adsorption efficiency through desorption process. But magnetite oxidized into maghemite/hematite with the increase of temperature. This transformation should be avoided to maintain the magnetic properties of magnetite. In this research magnetite separated from iron sand by magnetic extraction then coated with silica via sol gel method. The effect of drying temperature in sol gel had change the magnetite core structure into maghemite and found no formation of hematite at 350⁰C. Silica coating proved had protected magnetite from transformation into hematite due to drying temperature until 350⁰C .